2017
DOI: 10.1097/sla.0000000000001650
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Submucosal Tunneling Endoscopic Resection for Upper Gastrointestinal Submucosal Tumors

Abstract: STER is an effective and safe methodology for the resection of upper gastrointestinal submucosal tumors. Tumor size and shape impact on the piecemeal resection rate and procedural difficulty. STER for large tumors with irregular shape in the deep muscularis propria is also feasible but associated with relatively high risks of piecemeal resection and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 18 publications
6
80
1
1
Order By: Relevance
“…Seventeen original articles were considered appropriate for inclusion in this review [8-24]. Two articles [14,24] were from same institute and the time frames of these studies overlapped.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen original articles were considered appropriate for inclusion in this review [8-24]. Two articles [14,24] were from same institute and the time frames of these studies overlapped.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, therapeutic success was recorded for >77% of patients and en bloc resection was achieved in >85% of patients, while irregularly shaped or larger tumors were risk factors in piecemeal resection (33). Of the SMTs reported in these studies, >95% were leimyomas or gastrointestinal stromal tumors, while the other reported tumors included lipomas, schwannomas, calcifying fibrous, glomus, granular cell and nerve sheath tumors, proliferating collagen fibers, degenerated nodes and aberrant pancreatic tissue.…”
Section: Efficacy Of Stermentioning
confidence: 99%
“…Currently, >20 studies have been published with outcome data based on >700 patients (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)22,29,30,(32)(33)(34)(35). In these studies, therapeutic success was recorded for >77% of patients and en bloc resection was achieved in >85% of patients, while irregularly shaped or larger tumors were risk factors in piecemeal resection (33).…”
Section: Efficacy Of Stermentioning
confidence: 99%
“…Because of the limitation of the luminal size of the submucosal tunnel established by endoscopy most of those SETs are removed without too much surrounding tissue. In our experience, what is most important for complete resection is to keep the SET capsule intact during resection ( 4,5 ). Th erefore, a more practical and reasonable defi nition for complete resection of SETs by pathology is that a resected tumor has an intact capsule.…”
Section: Definition For Complete Resectionmentioning
confidence: 99%